(untitled) (A Social Science and Entrepreneurship Journal, 2024)
Digital leadership has become an important aspect in the transformation of the public sector in Indonesia. In the ever- growing digital era, leaders who are able to adopt and utilize information and communication technology effectively have the potential to achieve significant progress in public services. This abstract illustrates the importance of digital leadership in increasing the effectiveness of public services in Indonesia. This research involves literature study and data analysis related to digital leadership and the public sector in Indonesia. Research findings show that digital leadership can accelerate the digital transformation of the public sector and bring various benefits to society. Technology-oriented leaders are able to utilize digital tools to increase transparency, accountability, efficiency and public participation in the decision-making process. It is hoped that the results of this research will provide insight for public leaders, practitioners and academics to understand the important role of digital leadership in increasing the effectiveness of public services in Indonesia. By strengthening digital leadership, it is hoped that the public sector can adapt quickly to technological developments and provide public services that are more effective,